Pengaruh Corporate Social Responsibility Dan Good Corporate Governance Terhadap Nilai Perusahaan (Studi Empiris Pada Seluruh Perusahaan Yang Tercatat Di Bursa Efek Indonesia Periode 2009 – 2012) - Jacklyn Rambu Ariesti (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2014)
This Study Aims To Examine And Analyze The Influence Of Corporate Social Responsibility, Managerial Ownership, And Institutional Ownership, The Size Of Board Directors, The Size Of Board Of Commissioners, The Size Of Independent Board Of Commissioners, And The Size Of Audit Committee To The Value Of The Company. The Samples Used In This Study Are 33 Companies Listed On The Stock Exchange. The Sampling Method Is Purposive Sampling. Data Analysis Method Used In This Study Is Multiple Linear Regressions.Corporate Social Responsibility (Csr), Managerial Ownership, The Size Of Board Directors, The Size Of Board Of Commissioners Have Significant Negative Effect To The Value Of The Companies. Institutional Ownership, The Size Of Independent Board Of Commissioners And The Size Of Audit Committee Do Not Have Effect To The Value Of The Companies.Keywords: Corporate Social Responsibility, Good Corporate Governance, Firm Value